Review of the MRI brain findings of septo-optic dysplasia. Issue 2 (February 2021) - Ward, D.J.; Connolly, D.J.A.; Griffiths, P.D.
Abstract : AIM: To report the magnetic resonance imaging (MRI) findings from a retrospective case analysis of children with septo-optic dysplasia (SOD), a rare congenital disorder characterised by any combination of midline brain defects, optic nerve hypoplasia (ONH), and hypothalamic–pituitary dysfunction. MATERIALS AND METHODS: SOD was defined radiologically as complete or partial septum pellucidum (SP) absence with hypoplasia of at least one of the optic nerves and/or chiasm. Local MRI databases were searched for SOD cases in children over an 18-year period, and studies reviewed by two consultant paediatric neuroradiologists. The extent of structural SP, optic nerve, chiasm, and hypothalamic–pituitary involvement was recorded, along with coexisting brain abnormalities. RESULTS: Forty-eight cases of SOD were found; 44/48 (92%) demonstrated complete SP absence whereas 4/48 (8%) had partial absence. Eight of 48 cases (17%) exhibited unilateral ONH. Fifty-one percent of cases, where the pituitary was identified on MRI, demonstrated a structural pituitary abnormality, which included an ectopic posterior bright spot in 6%. The olfactory nerves were hypoplastic in 5/48 cases (10%). Twenty-seven of the 48 cases (56%) had another brain abnormality, resulting from some form of cortical formation abnormality/schizencephaly in 21/48 (44%). CONCLUSION: A high rate of associated brain abnormalities was found in the present cohort, including structural pituitary abnormalities in 51% and cortical formation abnormalities/schizencephaly in 44%. This suggests there is not a single cause for SOD, rather SOD is the phenotypic end point from multiple aetiological events. Individual children with SOD may have coexisting intracranial abnormalities, and, hence, high-quality MRI is required in all. Highlights: Septo-optic dysplasia is a rare congenital brain abnormality. Clinical and radiological findings in septo-optic dysplasia are highly variable. More than half of septo-optic dysplasia cases had a co-existing brain abnormality. Schizencephaly/other cortical formation abnormalities were seen in 44% of cases. Septo-optic dysplasia may be a phenotypic end point of multiple aetiological events.